2010
DOI: 10.1016/s0034-7094(10)70046-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Depth of the Epidural Space with the Use of Ultrasound

Abstract: The ultrasound is a precise tool to determine the depth of the epidural space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…The Pearson correlation coefficient reported by the individual studies ranged from 0.66 to 0.98. 23,26,30 The pooled Pearson product moment correlation coefficient was 0.91 (95% CI, 0.87-0.94), using a randomeffects model to account for heterogeneity, suggesting the ultrasound-measured depth of the epidural space was highly correlated with the depth of the epidural space measured during the epidural needle insertion (Fig. 2).…”
Section: Does Neuraxial Ultrasound Accurately Predict the Needle Insementioning
confidence: 98%
See 1 more Smart Citation
“…The Pearson correlation coefficient reported by the individual studies ranged from 0.66 to 0.98. 23,26,30 The pooled Pearson product moment correlation coefficient was 0.91 (95% CI, 0.87-0.94), using a randomeffects model to account for heterogeneity, suggesting the ultrasound-measured depth of the epidural space was highly correlated with the depth of the epidural space measured during the epidural needle insertion (Fig. 2).…”
Section: Does Neuraxial Ultrasound Accurately Predict the Needle Insementioning
confidence: 98%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32] Nine studies were performed in obstetric patients, 20,21,23,24,[27][28][29]31,32 3 in non-obstetric surgical patients (urology, vascular, and orthopedics), 22,26,30 and 1 in patients requiring a diagnostic lumbar puncture in the emergency department. 25 The quality of the studies was generally good, with the most common deficiency being unclear patient selection criteria.…”
Section: Does Neuraxial Ultrasound Accurately Predict the Needle Insementioning
confidence: 99%
“…This method was apparently very effective, because only 1 skin puncture was needed in all subjects (n = 60), and in 45% of the cases, redirection of the needle was necessary. Helayel et al 25 found no correlation between the need to reposition the needle after insertion and the difference they found between the 2 angles (measured at the transducer and at the needle with a protractor). This might suggest that the optimal obtained image by ultrasound resembles the optimal point of insertion as we defined in our study.…”
Section: Discussionmentioning
confidence: 95%
“…One might use a sterile protractor, as was done in the study by Helayel et al 25 To maximize puncture success rates, we hypothesize that some form of imaging support is necessary. The ultrasoundguided technique is increasingly used for neuraxial blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal US offer valuable information to facilitate neuroaxial blockade. Most previous studies focused on the epidural space 7,8 . We believe that US images could also provide accurate estimation of depth to reach intrathecal space.…”
Section: Introductionmentioning
confidence: 99%